Cryogenic Freezing of Silver Carp Spermatozoa for Conservation of Gene Pool - Hossain, MS; Sarder, MRI (Progressive Agriculture, 2013)
A series of experiments were conducted to develop and standardize the protocols for cryopreservation of sperm of silver carp (Hypophthalmicthys molitrix) with the view to conserve gene pool. Three extenders such as Alsevers solution, urea egg-yolk, egg-yolk citrate, and three cryoprotectants namely DMSO, methanol and ethanol were employed. Cryodiluents were prepared by mixing the cryoprotectants at 10% concentration of the extenders (%v/v). Milt and cryodiluents were mixed at a ratio of 1:9 for Alsevers solution and 1:4 for urea egg-yolk and egg-yolk citrate solutions. Alsevers solution, urea egg-yolk and egg-yolk citrate with DMSO found suitable for cryopreservation of sperm and it produced 81 ± 2.24%, 79 ± 5.48% and 74 ± 4.18% post-thawed spermatozoan motility respectively. In optimizing milt dilution, five dilution ratios (1 : 2, 1 : 4, 1 : 6, 1 : 9 and 1 : 12) were tested and among them 1:9 (milt: cryodiluent) demonstrated the highest post-thaw spermatozoan motility with Alsevers solution (76.67 ± 2.89%) and 1 : 4 produced the same with urea-egg-yolk (73.33 ± 2.8%) and egg-yolk citrate (76.67 ± 2.89%). As an optimum cryoprotectant fraction, 10% concentration was found effective to produce the highest spermatozoan motility for all three extenders. Sperm preserved with Alsevers solution, urea egg-yolk and egg-yolk citrate plus DMSO demonstrated the ability to fertilize eggs and produced hatchlings. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16861 Progress. Agric. 20(1 & 2): 99 106, 2009